Pulmonary Embolism in the Elderly: From Symptoms to Speckle Tracking Echocardiography - Christos Ballas; Dimitrios Sfairopoulos; Ioanna Samara; Lampros Lakkas; Olga Kardakari; Athanasios Konstantinidis; Katerina K. Naka; Lampros K. Michalis; Christos S. Katsouras (Journal of Cardiovascular Development and Disease)
(1) Background: There are little data about the differences in clinical and echocardiographic characteristics between elderly (aged ≥ 65 years) and younger patients with acute pulmonary embolism (PE). (2) Methods: Consecutive patients diagnosed with PE in a tertiary hospital were identified. Clinical characteristics, biomarkers and transthoracic echocardiography indices including right ventricular free wall longitudinal strain (RV-FWLS) were recorded. (3) Results: Of 200 patients enrolled, 19 patients had high-risk PE and were excluded from the study. Compared to younger patients, elderly patients with PE had less frequently pain and typical symptoms and more often were hospitalized due to another reason before the PE diagnosis. The elderly had higher values of D-dimer, high-sensitivity troponin I and brain natriuretic peptide (BNP). Echocardiographic differences were noted and the elderly had lower values of pulmonary vascular acceleration time, RV E/A ratio and lower tricuspid annular plane systolic excursion/pulmonary artery systolic pressure ratio. The RV-FWLS index did not show a statistically significant difference in distribution between age groups ≥ 65 and <65 years old. The RV diameter was similar across all age groups. (4) Conclusions: The elderly have differences compared with younger patients with PE regarding the mode of presentation, the values of biomarkers like D-dimer, BNP and troponins and some echocardiographic indices of RV affection.